Association of overtime work and hypertension in a Japanese working population: A cross-sectional study. (December 2014) - Imai, Teppei; Kuwahara, Keisuke; Nishihara, Akiko; Nakagawa, Tohru; Yamamoto, Shuichiro; Honda, Toru; Miyamoto, Toshiaki; Kochi, Takeshi; Eguchi, Masafumi; Uehara, Akihiko; Kuroda, Reiko; Omoto, Daisuke; et al.
<x xml:space="preserve">Abstract</x> Long working hours have been associated with an increased risk of cardiovascular disease, but its relationship with hypertension remains unclear. The objective of this study is to examine the relationship between overtime and presence of hypertension using data from a large-scale multi-company study in Japan. Participants were 52 365 workers of four companies that provided both health-checkup data and self-reported data on overtime worked. Hypertension was defined as systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥90 mmHg, and/or the use of antihypertensive drug. Logistic regression analysis was performed to determine the odds ratio for hypertension for each category of overtime work (<45, 45–79, 80–99 or ≥100 h/month) with adjustments for age, sex, company, smoking status and body mass index. The prevalence of hypertension tended to decrease with increasing overtime work: 17.5, 12.0, 11.1 and 9.1% for the shortest (<45 h/month) through the longest overtime category (≥100 h/month). The age-, sex- and company-adjusted odds ratios (95% confidence interval) were 1.00 (reference), 0.81 (0.75–0.86), 0.73 (0.62–0.86), 0.58 (0.44–0.76), respectively (p for linear trend <0.001). In a sub-cohort, the inverse association remained statistically significant after an additional adjustment for other potential confounders. Results of the present large-scale study among Japanese workers suggest an inverse association between overtime work and presence of hypertension.